The beginning of politics power in the biblical Book of Samuel - Halberṭal, Mosheh 1958-; Holmes, Stephen 1948- (Princeton, NJ Oxford Princeton University Press, 2017)
The grip of power -- Faces of political violence -- Dynasty and rupture -- David's will and last words
Notes bibliographique, index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Politics in the Bible; Power (Social sciences) -- Biblical teaching